2000
DOI: 10.1093/qjmed/93.8.523
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and clustering of serious clinical outcomes in antiphospholipid syndrome

Abstract: We assessed whether initial clinical presentations suggestive of antiphospholipid syndrome (APS) predicted the subsequent rate and type of serious clinical outcomes. Eighty-two consecutive patients with anticardiolipin antibodies or lupus anticoagulant were followed for 814 person-years after a first event suggestive of APS (livedo reticularis, thrombocytopenia, autoimmune haemolysis, thrombosis, central nervous system manifestations, recurrent abortions). The hazard of developing a second event was largest in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 24 publications
6
33
0
2
Order By: Relevance
“…Yet, no reliable prognostic autoantibodies could be identified that could predict transition. These results in association with results published by other investigators [15][16][17]21,22,24,25 suggest that PAPS may be considered as a potential pre-phase of transition towards other CTDs. …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Yet, no reliable prognostic autoantibodies could be identified that could predict transition. These results in association with results published by other investigators [15][16][17]21,22,24,25 suggest that PAPS may be considered as a potential pre-phase of transition towards other CTDs. …”
Section: Discussionsupporting
confidence: 90%
“…Altogether 65.4% of the patients remained in the undifferentiated CTD stage after 5 years, while complete regression occurred in 12.3% of patients. 14 In the present study we assessed the clinical and immunoserological characteristics of patients with 16 observed that the recurring event is similar to the previous thromboembolic events as arterial events were later followed by another arterial thromboembolic manifestation, while venous events were followed by recurrent venous thromboembolism. Mujic et al 17 followed 80 PAPS patients for 12 years and three cases developed SLE within 10 years.…”
Section: Discussionmentioning
confidence: 93%
“…A pivotal role of aPL in NPSLE and their predictive value for NP damage progression are well known [22][23][24][25][26][27][28][29][30][31][32] and substantially confirmed also by the present study. Other factors deemed as related to NP involvement have been previously proposed including high disease activity, caucasian ethnicity, presence of anti-Ro/SSA antibodies [20,21], vasculitis, nephritis, anti-dsDNA, LA and anti-Sm [23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 86%
“…We should caution that the classification criteria for APS and SLE are functional criteria and may not fully correspond to the subgrouping of APS and SLE based on genetic predisposition. APS is a remarkably heterogeneous syndrome with different prognostic profiles (35).…”
Section: Discussionmentioning
confidence: 99%